Labor Supply and the Payroll Tax: Note - Moffitt, Robert (American Economic Review, 1977)
In a recent paper in this Review, Duncan MacRae and Elizabeth MacRae perceived an important aspect of the labor-supply effects of the payroll tax namely, that the effect is crucially dependent upon the individual response to a kinked budget constraint. However, their actual conclusions on the direction of the response need major qualification. In particular, they assumed that all responses would be marginal, when in fact the possibility of nonmarginal response is always present when non-linear budget constraints shift. This latter possibility makes the labor-supply response much more ambiguous. This is illustrated in Figure 1 (modeled after Figure 1 of MacRae and MacRae). The budget constraint before the imposition of the tax is A B, giving the utility maximizer a choice of any income-leisure combination along AB. After the imposition of the tax composed of a marginal tax rate on earnings up to a maximum level of earnings E-the (disposable income) budget constraint is BDC. (Yn is the amount of nonlabor income.) At point D, the taxable maximum is reached. MacRae and MacRae assumed that an individual initially located above the maximum level (say, point II) would relocate along CD, resulting in an increase in labor supply if leisure is a normal good (the income effect); and that an individual below the maximum level (say, point I2) would relocate along BD, resulting in a decrease in labor supply if the substitution effect dominates the income effect. However, although this would occur for marginal changes, nonmarginal changes are also possible: an individual initially at II could relocate along BD, reducing labor supply; and an individual initially at I2 could relocate along CD, increasing labor supply. Both are possible and not in conflict with any of the assumptions (that leisure is a normal good or that the substitution effect dominates the income effect). Heuristically, imagine a shift from AB to CH, causing the individual at I, to definitely move to CD; a subsequent of DH to DB could easily induce the person to relocate along DB. Or, imagine a shift from AB to BG, causing the individual at I2 to definitely move to DB (under the assumptions); a subsequent pivot of DG to DC could easily induce the person to relocate along DC. Thus, the possibility of nonmarginal movements introduces more ambiguity than realized before.' As a sidelight, note that the labor-supply effects of an increase in the taxable maximum and of an increase in the tax ratepolicy alternatives that are currently being considered to raise revenue are both ambiguous for the same reasons. Figure 2 shows an increase in the tax rate as causing a shift from BDC to BD'C'. Those initially below the maximum level may decrease labor supply (marginally) or increase it (nonmarginally), while those above the maximum level may increase labor supply (marginally) or decrease it (nonmarginally). Figure 3 shows an increase in the taxable earnings maximum from E to E' as causing a shift from BDC to BD'C'. Although there is no response by those below the maximum (by revealed preference), those above may either increase labor supply (marginally) or decrease it (nonmarginally). The latter effect is likely to be stronger for this group than